CLAUSE BASED SEMANTIC PARSING - LOU, Jianguang; LIN, Zeqi; ZHANG, Dongmei (2023)
According to implementations of the subject matter described herein, a clause-based semantic parsing solution is provided. In the solution, a first clause with independent semantics is determined from a target statement. The target statement is converted to a first intermediate statement based on a first logical representation corresponding to the first clause. Subsequently, at least one logical representation corresponding to at least part of semantics of the first intermediate statement is determined. The first logical representation and the at least one logical representation may be used to determine a target logical representation corresponding to semantics of the target statement. Therefore, more accurate semantic parsing can be achieved.